Maramara me te Iwi Taketake: Data and the Indigenous Group - Cleave, Peter (Te Kaharoa, 2021)
This paper considers Indigenous groups and data. The paper begins with fifteen assorted questions which are addressed in various ways in the next two sections. The second section is a review of ‘Indigenous Data Sovereignty’ a collection by Kukutai and Taylor of 2016. This collection is seen as an excellent statement of the position of the Indigenous group regarding data and each chapter is reviewed in several paragraphs. Beginning with Kukutai and Taylor, the third and final section is a commentary on recent literature on data with reference to the Nation-state, Big Tech and Indigenous groups. This section considers a shifting situation involving machine learning and the hunting, gathering and farming of data. A reappraisal of the way data is used in the context of the Indigenous group, the Nation state and Big Tech is proposed. That reappraisal involves new considerations of identity in forms of ethnicity, nationalism and tribalism as well as the way Indigenous groups are defined by others and the ways in which they define themselves.